Magnetic horizons of ultra-high energy cosmic rays - Batista, R; Sigl, G (Deutsches Elektronen-Synchrotron, 2014)
The propagation of ultra-high energy cosmic rays in extragalactic magnetic fields can be diffusive, depending on the strength and properties of the fields. In some cases the propagation time of the particles can be comparable to the age of the universe, causing a suppression in the flux measured on Earth. In this work we use magnetic field distributions from cosmological simulations to assess the existence of a magnetic horizon at energies around 10$^{18}$ eV.